2014
DOI: 10.1039/c4ra08967g
|View full text |Cite
|
Sign up to set email alerts
|

CO2 splitting into CO and O2 in micro-tubular solid oxide electrolysers

Abstract: Efficient high temperature CO2 to CO and O2 conversion achieved using micro-tubular solid oxide electrolysers prepared by dual-layer co-extrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Later it was demonstrated that Ni–YSZ electrode possessed excellent electrochemical performance and high stability for CO 2 electrolysis in SOEC . Besides in planar SOECs, Ni–YSZ cathode also displayed admirable electrochemical performance for CO 2 electrolysis in microtubular SOEC . Normally, the product for CO 2 electrolysis or CO 2 /H 2 O coelectrolysis is CO or syngas (CO + H 2 ).…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Later it was demonstrated that Ni–YSZ electrode possessed excellent electrochemical performance and high stability for CO 2 electrolysis in SOEC . Besides in planar SOECs, Ni–YSZ cathode also displayed admirable electrochemical performance for CO 2 electrolysis in microtubular SOEC . Normally, the product for CO 2 electrolysis or CO 2 /H 2 O coelectrolysis is CO or syngas (CO + H 2 ).…”
Section: Cathode Materialsmentioning
confidence: 99%
“…In this study, the major objective is to prove the effectiveness of the new anodic current collector design in achieving a more uniform current collection and reducing contact loss. Therefore, a simplified method has been adopted to calculate various ohmic contributions, as described in previous studies [18,34]. It is generally accepted that the total ohmic loss is mainly composed of electrolyte ohmic loss, electrode ohmic loss, contact loss and resistance from current collector.…”
Section: Electrochemical Performances and Calculation Of Ohmic Contrimentioning
confidence: 99%
“…At these cases, small amount water was usually added to provide the proton. Besides, yttrium stabilized zirconia was also reported as the solid electrolyte for the electrochemical CO 2 splitting process in a micro‐tubular solid oxide electrolyzer . Without water providing proton, the O 2− generated on cathode transferred to anode to form O 2 with releasing electron.…”
Section: Fundamental Principlesmentioning
confidence: 99%